Fishery and utilisation of mesopelagic fishes and krill in the North Atlantic - Lamhauge, Súni; Arge Jacobsen, Jan; Willy Valdemarsen, John; Sigurdsso2, Thorsteinn; Bardarsson, Birkir; Filin, Anatoly (Copenhagen : Nordic Council of Ministers, 2008)
The main objective in this project was to explore the possibilities of commercial exploitation and utilisation of mesopelagic fish and krill, two groups of species that presently are not utilised commercially. The work was divided into three subtasks, to find and collect historic data and literature on mesopelagic fish and krill in the North Atlantic, with special emphasis to include important Russian literature to be translated, to study fishing gear and fishing technology, suitable to catch mesopelagic fish and krill in commercially acceptable catch rates, and to establish special awareness on the mesopelagic fish during future pelagic surveys. The most common mesopelagic species on both sides of the North Atlantic were Benthosema glaciale and Notoscopelus kroeyeri, and of krill or Euphausiids, the most the common species were Meganyctiphanes norvegica, Thysanoessa inermis, T. Longicaudata. The main conclusion from the present project was that in no case was the estimated density of mesopelagic fish and krill high enough for commercial utilisation in the Northeast Atlantic. This was also confirmed by analyses of existing and translated Russian literature. The concentration of the mesopelagic fish and krill ensembles was estimated to be less than 1 g/mm3, which is several orders to low for commercial utilisation with existing gear technology.